2021
DOI: 10.1136/bmjdrc-2020-001557
|View full text |Cite
|
Sign up to set email alerts
|

Clinical decision support to improve management of diabetes and dysglycemia in the hospital: a path to optimizing practice and outcomes

Abstract: IntroductionInnovative approaches are needed to design robust clinical decision support (CDS) to optimize hospital glycemic management. We piloted an electronic medical record (EMR), evidence-based algorithmic CDS tool in an academic center to alert clinicians in real time about gaps in care related to inpatient glucose control and insulin utilization, and to provide management recommendations.Research design and methodsThe tool was designed to identify clinical situations in need for action: (1) severe or rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Studies have demonstrated the need for improved transitions of care in hospitalized patients. [ 39 ] Glycemic management on the medical and surgical wards following an ICU transfer is an important transition of care that is high risk and could potentially be associated with gaps in care that could negatively impact patients’ safety and length of stay. In comparison to the ICU, patients receive less monitoring on the wards and the nurse-to-patient ratios are higher.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the need for improved transitions of care in hospitalized patients. [ 39 ] Glycemic management on the medical and surgical wards following an ICU transfer is an important transition of care that is high risk and could potentially be associated with gaps in care that could negatively impact patients’ safety and length of stay. In comparison to the ICU, patients receive less monitoring on the wards and the nurse-to-patient ratios are higher.…”
Section: Discussionmentioning
confidence: 99%
“…The 3.1% incidence of stress hyperglycemia in our study cohort denotes unequivocally elevated glucose values at which providers should consider treatment. Our detection criteria sustained a hospital-wide clinical decision support program employing real-time notifications and provision of practice recommendations 40 . Studies have reported a greater incidence in adult patients admitted to various hospital settings 1 , 3 , due to more inclusive criteria of hyperglycemia compared to our inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“… An algorithmic workflow codified to match common data elements corresponding to glycemic data and patient characteristics was used to recognize stress hyperglycemia events among hospitalized patients in real time. The algorithm was instituted as part of a hospital-wide program evaluating clinical decision support in the EHR with the purpose of addressing gaps in glycemic care by providing practice recommendations 40 . For the purpose of this study, we defined stress hyperglycemia among hospitalized patients as two point-of-care BG levels ≥ 10 mmol/L (180 mg/dL) at least 3 h apart within a 36-h-period during an inpatient encounter without documentation or biochemical evidence of diabetes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations